Material incentives moderate gender differences in cognitive effort among children - Paula Apascaritei; Jonas Radl; Madeline Swarr (Learning and Individual Differences, 2024)
Effort is crucial for academic performance and varies by gender. However, it is not clear at what age nor under what circumstances gender differences in effort arise. Using behavioral measures of executive function from 799 fifth-grade students, we find no gender differences in cognitive effort in the absence of rewards. However, boys exert more effort than girls when materially incentivized. Adding a status incentive on top of material rewards does not further increase the gender gap. According to expectancy-value theory, the degree to which incentives moderate the gender effect may depend on ability. We find that while low-ability girls work as hard as high-ability girls when no incentives are present, low-ability boys tend to disengage from effortful tasks. High-ability girls increase effort more than low-ability girls when material incentives are added, and high-ability boys increase effort more than low-ability boys when status incentives are added.
https://doi.org/10.21950/DEDRIZ
Keywords: 370; Cognitive effort; Gender; Incentives; Children; Laboratory experiments